Impact of Nutrition Education on Dietary Habits among Bachelor-in-Medicine, Bachelor-in-Surgery (MBBS) Students: A Study in an Indian Medical College - Kumar, Sudeep; Sah, Sumesh Prasad; Kumar, Dinesh; Arora, Manish; Sharma, Shiwani (Faculty of Medicine Universitas Padjadjaran, 2025)
Background: Unhealthy eating patterns, often triggered by academic pressures and erratic schedules, can negatively impact students’ health and hinder their ability to effectively guide future patients. Nutrition education offers a valuable opportunity to promote healthier eating habits by providing critical knowledge that supports both students’ personal wellbeing and professional competence.Objective: To evaluate the effect of nutrition education on eating habits of first-year Bachelor-in-Medicine, Bachelor-in-Surgery (MBBS) among medical students.Methods: A pre-post interventional study was carried out on 200 Phase-1 MBBS students of Muzaffarnagar Medical College between January and June 2024. Initial dietary habits were assessed using a validated questionnaire. A structured session of nutrition education was provided. The dietary habits were then re-assessed after four weeks, and changes were analyzed using paired statistical tests.Results: Data collected after the intervention showed notable enhancements in dietary practices. The percentage of students consuming three balanced meals a day increased from 32% to 68% (p < 0.001). The intake of fast food decreased from 65% to 35%, and the consumption of sugar-sweetened beverages fell from 58% to 30%. The average servings of fruits and vegetables consumed daily rose from 2.1 to 4.5 (p < 0.01). Nutrition knowledge scores presented a 30% improvement, indicating greater awareness.Conclusion: Medical students' eating habits are much improved by nutrition education, underscoring its significance in medical education. Future healthcare workers may benefit from lifelong good eating habits if such programs are incorporated into the curriculum, which would improve patient care and their own health.